The relationship between egg size and female size in freshwater crayfish, Astacus leptodactylus - Harlioglu, MM; Türkgülü, I (Kluwer Academic Publ, 2000)
[Abstract Not Available]
Keywords: carapace length; egg size; egg weight; fecundity estimates; freshwater crayfish (Astacus leptodactylus)